Peripheral ossifying fibroma: A clinical report - K S Poonacha; Anand L Shigli; Dayanand Shirol (Contemporary Clinical Dentistry, 2010)
The gingiva is often the site of localized growths that are considered to be reactive rather than neoplastic in nature. Many of these lesions are difficult to be identified clinically and can be identified as specific entity only on the basis of typical and consistent histomorphology. Peripheral ossifying fibroma is one such reactive lesion. It has been described with various synonyms and is believed to arise from the periodontal ligament comprising about 9% of all gingival growths. The size of the lesion is usually small, located mainly in the anterior maxilla with a higher predilection for females, and it is more common in the second decade of life. A clinical report of a 12-year-old girl with a large peripheral ossifying fibroma in the posterior maxilla showing significant growth and interference with occlusion is presented.